Cicada genus Pomponia Stål, 1866 (Hemiptera: Cicadidae) from Vietnam and Cambodia, with a new species, a new record, and a key to the species - Pham, Hong-Thai; Lee, Young June; Constant, Jerome (Zootaxa, 2015)
The genus Pomponia Stål, 1866 from Vietnam and Cambodia is reviewed . Pomponia brevialata Lee & Pham, sp. nov. is described from Vietnam. Pomponia backanensis Pham & Yang, 2009 is added to the Cambodian cicada fauna. A key to the seven Vietnamese and Cambodian species of the genus Pomponia Stål, 1866 is provided: P. linearis (Walker, 1850), P. backanensis Pham & Yang, 2009, P. brevialata Lee & Pham, sp. nov., P. subtilita Lee, 2009, P. piceata Distant, 1905, P. daklakensis Sanborn, 2009, and P. orientalis (Distant, 1912). Synonymic lists, information on geographical distributions, and material examined for the Vietnamese and Cambodian species of Pomponia are provided.